2004
DOI: 10.5034/inquiryjrnl_41.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Increased Medicare Expenditures for Physicians' Services: What are the Causes?

Abstract: In light of rising expenditures for physicians' services and the scheduled decreases in the amounts Medicare pays for such services, we identified the sources of change in the volume and intensity of Medicare physicians' services. We found that the per capita volume and intensity of physicians services used by Medicare beneficiaries increased more than 30% between 1993 and 1998. Our analyses indicated that, at most, half of this increase was due to measurable changes in the demographic composition, places of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…As one example, from 1980 to 1990 expenditures on acute hospital facility use by U.S. Medicare beneficiaries rose from $19,460 million to $47,842 million (146 percent) because of increased intensity (with per diem payments rising 190 percent) while the rate of discharges and days per discharge fell and the number of elderly beneficiaries rose by just 5.5 million (21 percent) and their average age by just 1/2 year (1 percent) (Health Care Financing Review 1998). An analysis of per capita Medicare physician resource use 1993-1998 found that virtually none of annualized 6 percent real growth could be attributed to the effects of aging, disease prevalence and distribution, or rapid technological change (Buntin et al 2004). Aging alone (increases in the number of elderly beneficiaries and increases in their average age) can therefore account for only a small fraction of the increase in Medicare expenditures.…”
Section: Review Of Empirical Results: Disparity Between Individual Anmentioning
confidence: 99%
See 1 more Smart Citation
“…As one example, from 1980 to 1990 expenditures on acute hospital facility use by U.S. Medicare beneficiaries rose from $19,460 million to $47,842 million (146 percent) because of increased intensity (with per diem payments rising 190 percent) while the rate of discharges and days per discharge fell and the number of elderly beneficiaries rose by just 5.5 million (21 percent) and their average age by just 1/2 year (1 percent) (Health Care Financing Review 1998). An analysis of per capita Medicare physician resource use 1993-1998 found that virtually none of annualized 6 percent real growth could be attributed to the effects of aging, disease prevalence and distribution, or rapid technological change (Buntin et al 2004). Aging alone (increases in the number of elderly beneficiaries and increases in their average age) can therefore account for only a small fraction of the increase in Medicare expenditures.…”
Section: Review Of Empirical Results: Disparity Between Individual Anmentioning
confidence: 99%
“…Related political culture measures of “egalitarianism,”“respect for authority,”“social solidarity,”“publicness,”“centralization,”“willingness to wait,” and so on have all been found to be statistically significant (or not) in some studies but not others, and all appear to be imprecise and ad hoc either in definition or application. “Technology” is frequently referred to as a causative factor, yet most econometric studies simply take the residual unexplained growth from a time series regression and term that a proxy measure for technological progress, and thus lack objective quantification that can be independently verified (Peden and Freeland 1998; Buntin et al 2004). Although “the residual” is clearly unsatisfactory as a measure of a major cause, the readily available alternatives (number of patents, lists of major medical breakthroughs, R&D spending) that can be measured in a fairly consistent and uncontroversial manner do not appear to provide significant explanatory power.…”
mentioning
confidence: 99%
“…al. [ 39 ] has found that the major reasons behind increasing intensity of physician services are measurable changes in the demographic composition, place of residence, prevalence of health conditions. Promoting generic drugs, reference pricing, incentivizing physicians and pharmacists, long-term value based and outcome-based pricing, public-private partnership can be effective ways for reducing drugs and diagnostic related expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Each CPT code is assigned an RVU number that is determined by the Centers for Medicare and Medicaid according to the complexity of the procedure. An RVU incorporates technical skill and work effort, practice expense, and professional liability 9 . In our study, the current and historical RVU number was matched to the CPT code of each patient's procedure 10 .…”
Section: Methodsmentioning
confidence: 99%